Effects of Different Topographic Positions on Soil Properties and Soil Enzymes Activities - DENGIZ, ORHAN; KIZILKAYA, RIDVAN; GO, CEYHUN; HEPSEN, SÜHEDA (Asian Journal of Chemistry, 2010)
The main objectives of this study were (i) to determine physical and chemical properties of six different soils (ii) to measure the range and degree of three soil enzyme activities, (iii) to evaluate the influence of soil properties on soil enzyme activities in the both sides of the Çankiri-Aciçay river associated with specific landforms and different slope gradient. While right side soils of the Aciçay river are formed on quaternary alluvial deposits that find on terrace and floodplain, left side soils formed from quaternary alluvium, alluvial-collivial material and oligomiocene gypsum and salt strata located on floodplain, terrace and steep lands, respectively. Soil properties data of both sides of Aciçay river soils indicated significantly differences each other in terms of pedogenic processes which have been shaped by landscape position and parent material. According to soil taxonomy, 6 different soils were determined and classified as entisol, inceptisol and mollisol along transect. In addition, it was found that changes of landscape positions associated with erosion and organic matter content can alter the soil enzyme activities within the soil profile and along different slope.